Seroprevalence of Specific Antibodies to Treponema pallidum in Blood Donors - Karki, S.; Tiwari, B. R.; Ghimire, P.; Maharjan, A; Rajkarnikar, M (Journal of Nepal Health Research Council, 2009)
Background: Detection of specific antibodies to Treponema pallidum in serum is correlated with present or past Syphilis. The study aimed to know the seroprevalence of syphilis among blood donors in relation to age, sex, type of donation and times of donation. Methods: A total of 24,000 blood donors were screened to detect the presence of specific antibodies against T. pallidum by enzyme linked immunosorbent assay (ELISA) according to standard test kit protocol. Initially reactive samples were reconfirmed by repeat testing and repeatedly reactive samples were considered seropositive for Syphilis. Results: The seroprevalence of specific antibodies to T. pallidum among blood donors was found 0.42% (95% CI= 0.3-0.5%). There was an increasing trends of syphilis as the age of the donors increased (Cochrane-armitage test, P < 0.001). The seroprevalence in males was 0.45% and in females was 0.24% (P >0.05), in first time donors was 0.36% and in repeated donors was 0.48% (P > 0.05), among volunteer donors was 0.41% and among replacement donors was 0.50% (P > 0.05). Conclusion: The similar seroprevalence in first time and repeat donors as well as in volunteer and replacement donors urges the need of more effective donor education and counselling. Key words: Blood donors; Seroprevalence; Specific treponemal antibodies; Syphilis. doi: 10.3126/jnhrc.v6i2.2212 Journal of Nepal Health Research Council, 2008 Oct;6(13): Page: 98-101